A micromechanical model for nano-metallic-multilayers with helium irradiation. (15th December 2016) - Yu, Long; Xiao, Xiazi; Chen, Lirong; Chu, Haijian; Duan, Huiling
Highlights: A micromechanical model is proposed for Cu/Nb NMMs with/without He irradiation. A composite grain model with interface effect is developed for NMMs. Numerical results of the theoretical model match well with experimental data. Abstract: Nano-metallic-multilayers (NMMs) have attractive irradiation-tolerant properties due to the high ratio of interfaces acting as effective sinks for irradiation-induced defects, like helium bubbles. The mechanical behaviour of NMMs can be affected by both interfaces and He bubbles, which is closely related to the layer thickness. In this work, the macroscopic mechanical behaviours of Cu/Nb multilayers with irradiation-induced He bubbles are explored by the crystal plasticity model (CPM) coupled with the elastic-viscoplastic self-consistent (EVPSC) method. At the microscale, hardening effects of He bubbles, interfaces and forest dislocations are evaluated by considering their influences on the critical shear resistance of dislocation movement. At the grain level, the equivalent mechanical properties of a composite grain consisting of different individual grains and interfaces are obtained by the Mori–Tanaka method. At the macroscale, the self-consistent scheme is adopted to predict the macroscopic mechanical behavior of NMMs which are made of composite grains. Numerical results of the proposed model match well with corresponding experimental data.